Установка для електромагнітного дозування рідкого металу підвищеної продуктивності - Гориславець, Ю.М.; Глухенький, О.І.; Глухенький, О.І.; Токаревський, А.В. (Технічна електродинаміка, 2012)
Structure and principle of operation of the installation for electromagnetic batching of lead alloys which is intended for production of metallic granules (shot) are described. The installation includes induction channel furnace, liquid-metal pump, electromagnetic batcher and water mold. Electromagnetic batcher implements forced capillary decay (fragmentation) of cylindrical jet of liquid metal in the range of 100...400 Hz. Obtained on this installation experimental results are presented. They are functions relating the diameter of metal particles, the height of metal over die, the frequency of induced decay and the rate coefficient of liquid metal with diameter of die, forming jet of melt.